Using Cross-Cultural Focus Groups as a Tool for Communication Campaign Design: An Example from Russia’s Forest Project - Eric A. Abbott; Kate Gouverniuk; Ludmila Liamets; Tatyana Ukhanova (Journal of Applied Communications, 2002)
Focus groups can be a useful tool when working on a cross-cultural communication project in which the communication specialist may have a very different cultural background than that of the target audience. Ten focus groups were used as a part of a large crosscultural project to design a forest fire public awareness campaign for Russia’s Far East and Siberia. Three of the focus groups were used to gain an in-depth understanding of forest behaviors that might pose a risk for forest fires. These groups also probed what members of the target audience believe would be reasonably safe behaviors. The remaining seven focus groups were used to test prototype campaign materials. This article offers practical advice on effective use of focus groups for any communicator involved in cross-cultural communication activities.